2007
DOI: 10.1167/7.14.8
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal dynamics of visual attention during saccade preparation: Independence and coupling between attention and movement planning

Abstract: During the preparation of a saccadic eye movement, a visual stimulus is more efficiently processed when it is spatially coincident with the saccadic target as compared to when the visual and the saccadic targets are displayed at different locations. We studied the coupling between visual selective attention and saccadic preparation by measuring orientation acuity of human subjects at different locations relative to the saccadic target and at different delays relative to the saccade cue onset. First, we general… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
149
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(177 citation statements)
references
References 34 publications
25
149
3
Order By: Relevance
“…6A). The onset of the movement cue (ST) may have initially perturbed attentional tracking of the moving object in the saccade task, a result that is in accordance with several studies showing that participants are unable to voluntarily monitor one eccentric location while preparing a saccade to another (Deubel and Schneider 1996;Montagnini and Castet 2007).…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…6A). The onset of the movement cue (ST) may have initially perturbed attentional tracking of the moving object in the saccade task, a result that is in accordance with several studies showing that participants are unable to voluntarily monitor one eccentric location while preparing a saccade to another (Deubel and Schneider 1996;Montagnini and Castet 2007).…”
Section: Resultssupporting
confidence: 77%
“…We have previously observed predictive updating of attention for both salient objects that captured spatial attention involuntarily (Jonikaitis et al 2013) and for locations attended as a target in a sequence of saccades (Rolfs et al 2011), but in neither of these studies did we observe a presaccadic drop in visual performance at the relevant location. Previous research has shown that participants are unable to voluntarily monitor one eccentric location while preparing a saccade to another (Deubel and Schneider 1996;Montagnini and Castet 2007), which has been interpreted as a competition of voluntary attention and saccade preparation for shared resources. Our findings suggest an updating of voluntary covert attention to the postsaccadic retinal coordinates of the attended objects.…”
Section: Discussionmentioning
confidence: 99%
“…However, without an anticipatory attention shift (Jonikaitis et al, 2013;Rolfs et al, 2011) localization of the cued position, even if facilitated by landmarks, would need to be followed by an attention shift to that position. The typical duration of an attention shift has been estimated to be 150-200 ms (Khayat, Spekreijse, & Roelfsema, 2006;Montagnini & Castet, 2007), a duration much longer than the average probe duration in our second experiment (44 ms). It is unlikely that an attention shift occurred to the cued location after the saccade, because this would not have yielded the early spatiotopic benefit found here and in other studies (Golomb, Pulido, et al, 2010;Jonikaitis et al, 2013).…”
Section: Discussionmentioning
confidence: 52%
“…Thus, it appears that neuronal signals originating in oculomotor centers can trigger the effects of covert attention near the spatial position encoded by the stimulated neurons (Cutrell and Marrocco, 2002;Moore and Armstrong, 2003), even in the absence of an eye movement. This suggests that the pathways conveying extraretinal signals related to the saccade are responsible for psychophysical observations on the increased perceptual saliency of visual objects near the saccade target (Kowler et al, 1995;Deubel and Schneider, 1996;Castet et al, 2006;Montagnini and Castet, 2007).…”
Section: Functional Considerationsmentioning
confidence: 95%
“…These authors present a computational theory that also predicts two other phenomena known to occur perisaccadically: receptive field shifts (Duhamel et al, 1992) and enhanced visual discrimination at the saccade target (Kowler et al, 1995;Deubel and Schneider, 1996;Castet et al, 2006;Montagnini and Castet, 2007). The model incorporates a detailed mathematical description of the spatial and temporal factors that affect perisaccadic perception, and relates these factors to specific brain structures.…”
Section: Comparison To Other Modelsmentioning
confidence: 99%